2022
DOI: 10.1123/ijspp.2022-0094
|View full text |Cite
|
Sign up to set email alerts
|

Association of Muscle Strength With Muscle Thickness and Motor Unit Firing Pattern of Vastus Lateralis Muscle in Youth Athletes

Abstract: Purpose: Contributions of neural and muscular factors to muscle strength change with growth, but such changes remain unclear in young populations. This study aimed to clarify the association between muscle strength and neural and muscular factors in youth athletes. Methods: Maximal voluntary contraction (MVC) during isometric knee extension, the motor unit firing rate (MUFR), and muscle thickness (MT) of the vastus lateralis were measured in 70 youth male soccer players (mean [SD]; chronological age = 16.3 [0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…We analyzed the correlation between RAT and Young’s modulus at three time points and found that these two parameters exhibited a weak positive correlation, which is consistent with the results of the study by Peter et al Therefore, we believe that the RAT and stiffness of the rectus abdominis muscle may reflect physiological characteristics such as rectus abdominis muscle strength. Thicker muscles have relatively higher stiffness and muscle strength ( Misirlioglu et al, 2021 ; Yoshimura et al, 2022 ), which beneficial for counteracting the traction of the growing abdominal cavity on both rectus abdominis muscles during pregnancy and facilitates the recovery of the muscle and shrinkage of the IRD during postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the correlation between RAT and Young’s modulus at three time points and found that these two parameters exhibited a weak positive correlation, which is consistent with the results of the study by Peter et al Therefore, we believe that the RAT and stiffness of the rectus abdominis muscle may reflect physiological characteristics such as rectus abdominis muscle strength. Thicker muscles have relatively higher stiffness and muscle strength ( Misirlioglu et al, 2021 ; Yoshimura et al, 2022 ), which beneficial for counteracting the traction of the growing abdominal cavity on both rectus abdominis muscles during pregnancy and facilitates the recovery of the muscle and shrinkage of the IRD during postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…Using a different approach, Yoshimura et al (2022) conducted an electromyographic and ultrasound based setup to clarify the link among muscle strength and neural and morphological factors in youth athletes. The results showed a significant correlation between muscle strength and muscle thickness, but not motor unit firing rate.…”
Section: Introductionmentioning
confidence: 99%